Hymenoptera venom allergy and immunotherapy - what a General Practitioner should know - Mazurkiewicz, Zuzanna; Hak, Zofia; Pilszyk, Zuzanna; Pilszyk, Aleksandra; Gomułka, Krzysztof (Family Medicine & Primary Care Review, 2021)
Due to the common prevalence of Hymenoptera, stings and bites are a well-known problem in society. Most often they are not life threatening, but for a group of people who are allergic to this venom, they are a significant problem. Although stinging species are widely known, patients often have a problem distinguishing between bee and wasp stings. Because of this, it is very important to educate people about Hymenoptera species, as well as about post-sting procedures. The consequences of exposure to venom can be serious, but there are solutions that can significantly affect the quality of life of people who are allergic to venom. One of these is equipping the patient with adrenaline auto-injectors, another is venom immunotherapy. In choosing the right method, it is crucial to gather a medical history and check if the patient meets certain guidelines. It is also important if there are other factors that are exceptions to the guidelines. Patients who are concerned with their reaction to Hymenoptera venom often turn to the General Practitioner first. This is why proper education and well-chosen medical treatment are so important at the primary care level. Providing relevant information and providing medical care can significantly increase the quality of life of patients.